Influence of the Application of Rosemary Essential Oil (Salvia rosmarinus) on the Sensory Characteristics and Microbiological Quality of Minimally Processed Pumpkin (Cucurbita moschata) - Benites, Julio Federico; Gutiérrez, Diego Ricardo; Ruiz, Silvana Cecilia; Rodriguez, Silvia del Carmen (MDPI, 2025)
Artículo presentado al 5th International Electronic Conference on Foods, 28–30 October 2024